A Simple Primary Amide for the Selective Recovery of Gold from Secondary Resources. Issue 40 (24th August 2016) - Doidge, Euan D.; Carson, Innis; Tasker, Peter A.; Ellis, Ross J.; Morrison, Carole A.; Love, Jason B.
Abstract: Waste electrical and electronic equipment (WEEE) such as mobile phones contains a plethora of metals of which gold is by far the most valuable. Herein a simple primary amide is described that achieves the selective separation of gold from a mixture of metals typically found in mobile phones by extraction into toluene from an aqueous HCl solution; unlike current processes, reverse phase transfer is achieved simply using water. Phase transfer occurs by dynamic assembly of protonated and neutral amides with [AuCl4 ] − ions through hydrogen bonding in the organic phase, as shown by EXAFS, mass spectrometry measurements, and computational calculations, and supported by distribution coefficient analysis. The fundamental chemical understanding gained herein should be integral to the development of metal‐recovery processes, in particular through the use of dynamic assembly processes to build complexity from simplicity. Abstract : Going for gold : A simple primary amide is shown to be an effective reagent for the selective recovery of gold by solvent extraction from a mixture of metals representative of those in waste electrical and electronic equipment (WEEE). The recovery is achieved through the formation of dynamically assembled hydrogen‐bonded amide/AuCl4 clusters.